An Economic Overview of BIMSTEC Countries: (1997-2011) - Chowdhury, Amit Bikram; Neogi, Debasis (Journal of Asian Business Strategy, 2013)
The Bay of Bengal Initiative for Multi-Sectoral Technical and Economic Cooperation (BIMSTEC) brings together Nepal, Bhutan, Bangladesh, Srilanka, Myanmar, Thailand and India for cooperation in Trade, Industry and sectors of mutual interest. It aimed to establish a unique link between South Asia and South East Asia. The seven BIMSTEC countries are widely different with respect to size, level of development and economic structure. This article investigates the economic situation in each BIMSTEC country during the 1997-2011 periods. In general, the economic performance of the BIMSTEC economies is influenced by three major sets of factors, namely external impacts, policy responses, and structural factors. The present paper aims to investigate the macro-economic indicators and analyse their effects on economic performance of each BIMSTEC country during the 1997-2011 period. The paper highlights the nature of trade in the different sectors among the BIMSTEC countries. This paper also tries to analyse business prospect in this region. The overview of the region provides an indication of the possibility of expansion of trade in future.